(untitled) (Global Journal of Science Frontier Research, 2017)
A participatory rural appraisal was performed in order to identify farmers’ pearl millet production constraints, preferred varietal traits and their knowledge about Striga hermonthica. This was conducted in Dutse (Madobi and Kudai), Birninkudu (Kantoga and Kafingana) and Kiyawa (Karfawa and Shuwarin) local governments of Jigawa state Nigeria. Questionnaires and focus group discussion were used to gather information from 143 respondents. Results shows that the five most important traits selected were resistance to Striga infestation, resistance to downy mildew, tolerance to shattering, good quality local beverage, and tolerance to lodging. The major constraints to production across all the districts were low soil fertility, Striga, downy mildew, and high labour costs. Farmers had a good knowledge about Striga and their control methods across the locations were hand-pulling and or hoe weeding.